The Development Of Collision Module Based On Process Image For Physics Learning In Senior High School - Rony Harianto; Arif Harimukti; Sutarto Sutarto; Indrawati Indrawati (Pancaran Pendidikan, 2017)
The processed image is defined as a series of images of objects, events or phenomena, which the images of one and another are relatively different in terms of circumstances, position, shape, or their combinations, as a whole describes a coherent phase and a unified whole. The aim of this research is to produce a module based on process image that appropriates for independently learning mechanics (circular motion) of students in senior high school. The appropriateness of the module is shown by validity, effectivity, and practicality of the module as a printed media that suit for learning of circular motion in high school. This research is a research and development, by using Four-D (Define, Design, Develop, Disseminate) design. The subject of this research is students class XI senior high school. This time, we still work in two stages (define and design), so we have produced the module hypothetically.